Duopoly Competition with Network Effects in Discrete Choice Models - Chen, Ningyuan; Chen, Ying-Ju (Operations Research, 2021)
It has been realized for a long time that network effects play an important role in how market participants compete with each other. Arguably, companies like Facebook and Google are able to gain immense market power by leveraging the network effects of their consumers, despite potential competitors. This paper investigates how the dynamics play out in duopoly competition. We find that when the network effects per unit of consumption are weak, the competitors can co-exist and gain even market shares. As network effects become stronger, it is unstable, and even impossible, for the firms to coexist, and one firm emerges victorious, taking the majority of the market. The study provides a theoretical analysis for commonly observed market phenomena. It may also have implications for antitrust legislation: Special policies need to be created to maintain a competitive market structure for products and services with strong network effects.